1999
DOI: 10.1038/sj.onc.1202418
|View full text |Cite
|
Sign up to set email alerts
|

Over-representation of a germline RET sequence variant in patients with sporadic medullary thyroid carcinoma and somatic RET codon 918 mutation

Abstract: The aetiology of sporadic medullary thyroid carcinoma is unknown. About 50% harbour a somatic mutation at codon 918 of RET (M918T). To investigate whether other RET sequence variants may be associated with or predispose to the development of sporadic medullary thyroid carcinoma, we analysed genomic DNA from the germline and corresponding tumour from 50 patients to identify RET sequence variants. In one patient, tumour DNA showed a novel somatic 12 bp in-frame deletion in exon 15. More interestingly, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
114
4
11

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 131 publications
(148 citation statements)
references
References 26 publications
(23 reference statements)
19
114
4
11
Order By: Relevance
“…It may be suggested that the GGT?AGT polymorphism causes the creation of a cryptic splice donor, splice acceptor or splice enhancer, therefore leading to an altered protein that may contribute to the development of C-cell hyperplasia. Similar mechanisms have been previously hypothesised in the cases of polymorphisms associated with sporadic MTC and Hirschsprung disease (Borrego et al, 1999;Fitze et al, 1999;Gimm et al, 1999). Unfortunately, RNA from our radio-induced thyroid tumours was not available to test this hypothesis.…”
Section: Discussionsupporting
confidence: 73%
“…It may be suggested that the GGT?AGT polymorphism causes the creation of a cryptic splice donor, splice acceptor or splice enhancer, therefore leading to an altered protein that may contribute to the development of C-cell hyperplasia. Similar mechanisms have been previously hypothesised in the cases of polymorphisms associated with sporadic MTC and Hirschsprung disease (Borrego et al, 1999;Fitze et al, 1999;Gimm et al, 1999). Unfortunately, RNA from our radio-induced thyroid tumours was not available to test this hypothesis.…”
Section: Discussionsupporting
confidence: 73%
“…In a previous study, we showed that somatic mutations in NTRK1 are not common in sporadic MTCs. 10 In the present study, we did not find any somatic mutations of NTRK2 and NTRK3 in tumor DNA from 31 independent patients with sporadic MTC. Hence, we conclude that sequence variants in these genes are not likely to be responsible for differences in expression at the protein level, as previously reported.…”
Section: Discussionmentioning
confidence: 62%
“…Mutation analysis, however, did not reveal any non-polymorphic sequence variants. 10 In agreement with this finding, immunohistochemical analysis instead suggested a role for NTRK2 (also known as TRKB 16 ) and NTRK3 (also known as TRKC 17 ), which are also neurotrophin receptors, in the pathogenesis of MTC. 17 In advanced stages of MTC, NTRK2 expression was substantially reduced compared to NTRK3 expression, which was increased.…”
mentioning
confidence: 48%
See 2 more Smart Citations